(untitled) - Jarvis, Carolyn (St. Louis ( Missouri ), 2004)
This comprehensive student workbook is prepared by Carolyn Jarvis to accompany the core text, Physical Examination and Health Assessment, 4th Edition. It contains the following elements for each chapter:Purpose, Reading assignment, Audio-visual assignment, Glossary of key terms, Study guide with a variety of learning activities, including multiple-choice review questions, short answer, anatomy and physiology review, and matching Assessment video critical thinking questions, Clinical objectives Regional write-up sheets, Student performance checklists. Appendixes include answers to review questions, as well as several helpful reference charts.
Keywords: Physical diagnosis.,Nursing assessment